Living Conditions and Asset Ownership for the Host and Rohingya Populations in Cox's Bazar - World Bank (World Bank, Washington, DC, 2021)
The modules on housing characteristics and assets were administered as part of the household questionnaire of the Cox’s Bazar Panel Survey (CBPS) to the household head or an adult member (age 15+) with substantial knowledge about the daily activities of the household. Data was collected from 5,020 households across camp and host settlements (Camp settlements are defined as areas within the camp boundaries set by the government, UNHCR and IOM jointly. Host settlements are defined as all areas outside of the camp boundaries), on topics of housing conditions and asset holdings. This includes information on the construction material of housing, water and sanitation facilities, lighting and electricity usage, and current and past ownership of assets. The module generates representative statistics for hosts and displaced Rohingya population in Cox’s Bazar; and it can be further disaggregated into hosting areas with low and high exposure to the Rohingya influx